2012
DOI: 10.1089/jwh.2011.3009
|View full text |Cite
|
Sign up to set email alerts
|

Vitamin D Deficiency in Postmenopausal Breast Cancer Survivors

Abstract: Purpose: Breast cancer survivors (BCS) taking aromatase inhibitors (AIs) are at an increased risk for decreased bone density and fractures. Given the role vitamin D plays in bone metabolism, we examined the prevalence of and risk factors for vitamin D deficiency in a study of postmenopausal BCS on AIs. Methods: We collected data on 391 postmenopausal women with stage I-III breast cancer on AI therapy. Vitamin D levels were measured by radioimmunoassay from patients' sera; deficiency was defined as a level < 30… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
21
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 23 publications
(25 citation statements)
references
References 38 publications
3
21
1
Order By: Relevance
“…In our study of breast cancer patients, the first among Chinese women, we found that higher BMI was associated with vitamin D deficiency, as has been found in other studies of breast cancer patients [8], [14], [16]. These findings confirm the well-known associations of lower vitamin D levels with higher BMI observed in healthy adult populations [26][28].…”
Section: Discussionsupporting
confidence: 91%
“…In our study of breast cancer patients, the first among Chinese women, we found that higher BMI was associated with vitamin D deficiency, as has been found in other studies of breast cancer patients [8], [14], [16]. These findings confirm the well-known associations of lower vitamin D levels with higher BMI observed in healthy adult populations [26][28].…”
Section: Discussionsupporting
confidence: 91%
“…As in line with Vrieling et al's study (2011), we did not find clear differences in RT or HT use versus low levels of 25-OHD. Various studies have also shown that obesity and lower physical activity are associated with low serum levels of vitamin D in patients with BC (Lagunova et al, 2010;Vrieling et al, 2011;Friedman et al, 2012). In our study, according to the univariate analysis BMI>25 was found significantly associated with low levels of vitamin D levels, however correlation was not significant in multivariate analysis.…”
Section: Discussioncontrasting
confidence: 51%
“…Risk factors for vitamin D deficiency include nonCaucasian race [5,6], living in northern latitudes, winter season [7], high BMI [8][9][10][11], diabetes mellitus Type 2 [11,12] and increasing age [13], among others. Non-Caucasian race and obesity have been confirmed by our group to be risk factors in postmenopausal breast cancer survivors [14].…”
Section: Vitamin D and Breast Cancer Vitamin D Levels And Clinical Deficisupporting
confidence: 53%